Computer Assisted Learning (CAL) in Mathematics and Personal Success of Elementary School Girls - Noriany, Orli (Wydawnictwo Naukowe Uniwersytetu im.Adama Mickiewicza w Poznaniu, 2013)
Standardized tests administered nationwide in the fth grade of the elementary school in Israel have shown that in the subject of mathematics boys achieve signi cantly higher scores than do girls. This gap is worrisome because of the importance of mathematical skills in success in education, both in the secondary school and in higher education, and in the job market. This paper brie y reviews a number of possible reasons for this gap, including lack of suitability to girls of current instruction methods in frameworks of mixed-gender education, de ciencies in mathematics training and math anxiety among teachers, gender stereotypes, and the phenomenon of the self-ful lling prophecy. Then the paper outlines the researcher’s proposed method, Computer Assisted Learning (CAL), for promoting girls’ achievements in mathematics. Initial results have been promising.
Komputerowe wspomaganie uczenia sie matematyki i sukces osobisty uczennic szkoły podstawowej
Keywords: mixed-gender education; achievement of girls; di erential attitudes to boys and girls; computerized; assignments